Reporting and follow-up recommendations for performance audit in SAI in the Republic of Serbia - Aleksandar Popović (Economic Themes, 2020)
Development of an integrated audit approach in state auditing enabled, in addition to financial audit and audit of regulatory compliance, audit of the public sector's entities performance at the same time. Thus performance audit (success, value-for-money) gets primacy within the scope of activity of the supreme audit institutions. The goal of such an activity is to point to the development and importance of auditing effectiveness in the State Audit Institution (SAI) in the Republic of Serbia, emphasising reporting on performance auditing, detected irregularities in the use of budgetary resources and recommendations made to the public sector entities by SAI, as well as following them up for the purpose of more effective management and use of state property and state funds.
Keywords: M42; 330; SAI; performance auditing; reporting; recommendations; follow-up